Strengthening the Creative Dimension in Learning Islamic Religious Education and Character Through Project Based Learning Model - Madania, Siti Makiyatul; Yusuf, Wiwin Fachrudin (Al-Fikru: Jurnal Ilmiah, 2025)
Islamic Education and Moral Education in many schools, including Darut Taqwa High School, is still dominated by lecture methods, which result in low student participation and creativity. This condition encourages the need for more active and contextual learning innovations. This study aims to examine the strengthening of the creative dimension in Islamic Education and Character Education through the implementation of the Project-Based Learning model at SMA Darut Taqwa. This study uses a descriptive qualitative approach with data collection techniques consisting of observation, interviews, and documentation, and analyzed using the interactive model of Miles and Huberman. The results of the study indicate that the implementation of Project-Based Learning is able to increase student active involvement, encourage creativity, and produce original works that are relevant to daily life. Teachers act as facilitators who guide the learning process to be more meaningful and contextual. The implications of this study indicate the importance of teacher training to master project-based learning models and the need for school support to create a learning environment that supports character building and creativity in accordance with the objectives of the Merdeka Curriculum.